Combustion performance and emission characteristics of a diesel engine burning biodiesel blended with n-butanol. (15th December 2019) - Xiao, Helin; Guo, Fengyun; Li, Shengjun; Wang, Ru; Yang, Xiaolong
Abstract: The combustion and emission characteristics of a four-cylinder direct injection diesel engine fueled with 0%, 10%, 20% or 30% blends of n-butanol and biodiesel were characterized at the loads of 0.13–1.13 MPa brake mean effective pressure (BMEP) and the speed of 1800 rpm. With the main injection time and rotation speed constant in the bench test, the cylinder pressure, heat release rate, ignition delay and the regulated or unregulated emissions were measured. The peak of HRR maximized at 0.38 MPa BMEP. The ignition delay period was prolonged in the case of n-butanol. But the combustion duration was shorten with the rising of n-butanol ratio. When n-butanol was added, more HC, NOx and acetaldehyde and less CO, 1, 3-butadiene and benzene were emitted. For soot emissions, the addition of n-butanol would reduce the formation of soot. In conclusion, the addition of n-butanol improves the combustion performance while there has different changes about emission characteristics.